Necessity entrepreneurship and industry choice in new firm creation - Nikiforou, Argyro; Dencker, John C.; Gruber, Marc (Strategic Management Journal, 2019)
Abstract Research Summary Research on necessity entrepreneurship has generated important insights, yet it views necessity entrepreneurs in developed countries as one encompassing group of unemployed individuals—ignoring that the level of need is not uniform but instead increases with time spent in unemployment. We begin to unpack the role of unemployment duration in necessity entrepreneurship by asking how it affects one of the most fundamental decisions in start‐ups: “what business should I be in?” Analyzing primary data on 576 necessity entrepreneurs combined with three secondary data sets, we find that unemployment duration affects whether ventures are launched in “home” or in external industries, and moderates the extent to which founders' industry experience and the attractiveness of external opportunities relative to those in the “home” industry shape industry choice. Managerial Summary Necessity entrepreneurs—individuals who create new firms because they have no other options for work—represent a substantial proportion of world‐wide entrepreneurial activity, and, in developed countries, often come from the ranks of the unemployed. We analyze these entrepreneurs by answering the question “what business should I be in?,” a fundamental strategic decision that founders make. Our findings reveal that duration in unemployment is a key, hitherto unexamined factor that systematically affects the industry‐choice decision in startups. Moreover, we find that duration of unemployment moderates the founder's industry experience and the attractiveness of external opportunities relative to those in the “home” industry, with a markedly different picture for the long‐term unemployed—suggesting the need for customized government policies for formerly unemployed entrepreneurs.